Visual of Atraction: Media, Soft-Campaign, and the Art of Persuade Muslimah to do Exercise - Sariyanti, Lilis (Malikussaleh Social and Political Reviews, 2024)
This article discusses efforts to fulfill the facilities and rights of Muslim women when using public spaces for exercise. Fulfillment of this right is seen based on the presence of sports products that carry the syari concept, one of which is syari sportswear products. Alur Cerita is present as one of the brands that produce syari sportswear. However, through Alur Cerita, the author reviews how the Alur Cerita brand was built and known to the public through social media? How does the Alur Cerita brand build the concept of visual attraction through social media as art to fulfill the needs of Muslim women to exercise in public spaces and is there a connection with the Islamic market? To answer some of these questions, this research was written using a qualitative descriptive approach and elaborated using virtual ethnographic methods. Overall data collection in this research was carried out by collecting data online and supported by several relevant literature. The results of this research are that Alur Cerita is not only present as a syar'i brand, but also takes a role in carrying out Islamic market activities. Then, Alur Cerita has also become an Islamic commodity that is used not only to fulfill Muslim women's needs, but also as an effort aimed at making a profit. In addition, branding techniques are used well in the form of soft campaigns to convey persuasive narratives for Muslim women.